Landslides on mountain roads: a calculation proposal of the sliding block - Picado, Juan Antonio (2018)
For the determination of possible landslides on the slopes bordering roads, especially those that go through mountainous formations, of topographies of great slopes, a pseudo-static method is proposed, for purely cohesive soils, based on the theory that weathering occurs as a result of weathering and the humidity of the superficial rock of the mountains, combines the variables of slope, humidity, weight of the vegetal cover and of the soil. The investigation aims to obtain values that allow people to predict landslides. Moreover, this would allow to mitigate the vulnerability of the susceptible zones to them, what would prevent accidents, anda saving in time and machinery.